Answer: y= -x-5
Step 1: Determine which equation to change
Since we will be using the substitution method, we will need to substitute y from the bottom equation with information from the top equation. This will be the equation we change.
Step 2: Change the equation
Let’s rewrite the equation we will be working with.
3x+3y= -15
Our goal will be to get y alone on the left side. To start, let’s subtract 3x from both sides, leaving only 3y on the left side.
3x+3y= -15
3y= -3x-15
Now we need to get y completely alone by eliminating the coefficient of 3. Let’s do this by dividing each term by 3.
3y= -3x-15
y= -x-5
This is your answer. Hope this helps! Comment below for more questions.
Answer:
Solution :
********************************************
Two angles are said to be a pair of
adjacent angles if they have a common
arm and lie on the either sides of the
common arm .
***********************************************
Now ,
i ) a , b are a pair of adjecent angles .
ii ) c , d are pair of adjecent angles.
iii ) e, f are not adjecent angles .
Step-by-step explanation:
Jax gets 4 packs per month...each pack contains 4 cards...so he gets 16 cards per month.
Sofia gets 3 packs per month..each pack contains 4 cards...so she gets 12 cards per month..
56 + 16m = 68 + 12m
16m - 12m = 68 - 56
4m = 12
m = 12/4
m = 3.....they will have the same number of cards in 3 months
Jax : 56 + 16(3) = 104 cards
Sofia : 68 + 12(3) = 104 cards
and they will both have 104 cards
Answer:
20.39
Step-by-step explanation:
35.99 – 15.6 = 20.39
Answer:
y = 2
Step-by-step explanation:
Addition Method:
4x - 2y = 6
2x + y = 7
-2(2x + y) = -2(7)
4x - 2y = 6
-4x - 2y = -14
-4y = -8
y = 2
Substitution Method:
4x - 2y = 6
2x + y = 7
-2y = 6 - 4x
2y = 4x - 6
y = 2x - 3
2x + (2x - 3) = 7
4x - 3 = 7
4x = 10
x = 2.5
2(2.5) + y = 7
5 + y = 7
y = 2
Brainliest, please :)